De-escalation of antiplatelet therapy in acute coronary syndromes: Why, how and when? - Galli, Mattia; Angiolillo, Dominick J. (Frontiers in Cardiovascular Medicine, 2022)
The synergistic blockade of the key platelet signaling pathways of cyclooxygenase-1 blockade and P2Y12 signaling by combining aspirin plus a potent P2Y12 inhibitor (prasugrel or ticagrelor), the so called dual antiplatelet treatment (DAPT), has represented the antithrombotic regimen of choice in patients with acute coronary syndrome (ACS) for nearly a decade. Nevertheless, the use of such antiplatelet treatment regimen, while reduced the risk of thrombotic complications, it is inevitably associated with increased bleeding and this risk may outweigh the benefit of a reduction of ischemic events in specific subgroup of patients. In light of the adverse prognostic implications of a bleeding complication, there has been a great interest in the development of antiplatelet regimens aimed at reducing bleeding without any trade-off in ischemic events. The fact that the ischemic risk is highest in the early phase after an ACS while the risk of bleeding remains relatively stable over time has represented the rationale for the implementation of a more intense antithrombotic regimen early after an ACS, followed by a less intense antithrombotic regimen thereafter. This practice, known as a “de-escalation” strategy, represents one of the more promising approaches for personalization of antithrombotic therapy in ACS. In this review we discuss the rationale, appraise the evidence and provide practical recommendations on the use of a de-escalation strategy of antiplatelet therapy in patients with an ACS.